Exposure to phthalates and bisphenol analogues among childbearing-aged women in Korea: Influencing factors and potential health risks. (February 2021) - Mok, Sori; Jeong, Yunsun; Park, Minkyu; Kim, Sunmi; Lee, Inae; Park, Jeongim; Kim, Sungkyoon; Choi, Kyungho; Moon, Hyo-Bang
Abstract: Phthalates and bisphenol A (BPA), widely applied in industrial and consumer products, can affect hormones associated with the human reproductive system. Because the incidence of reproductive diseases is increasing, a comprehensive exposure assessment of phthalates and bisphenol analogues (BPs) is required for childbearing-aged women. Phthalate metabolites and BPs were measured in urine samples collected from 509 childbearing-aged women (20–48 years) in Korea to investigate their current exposure status, profiles, influencing factors, and potential health risks. DEHP metabolites and BPA were the dominant compounds found, indicating that they are highly consumed in daily life. Bisphenol S (BPS), as an alternative to BPA, was detected in most urine samples. Total concentrations of phthalate metabolites and BPs ranged from 3.42 to 3570 (GM: 45.6) ng/mL and from <LOQ to 80.3 (0.91) ng/mL, respectively, which were within the ranges observed in women in previous studies. Exposure to diethyl phthalate (DEP) was significantly associated with the use of cosmetics and personal care products such as perfume, body lotion, and sunscreen. Higher ratios of urinary BPS/BPA were observed in younger and more highly educated women and in women living in urbanized regions than others. This result suggests that a shift in consumption from BPA to BPS was preferentially occurring in urbanized regions. The assessment of the cumulative risk posed by phthalates and BPs showed that they pose only a small health risk to Korean women. This study provides baseline data on exposure levels, profiles, and influencing factors for phthalates and BPs in childbearing-aged women. Graphical abstract: Image 1 Highlights: A wide range of exposure to phthalates and bisphenols was observed in Korean women. Urinary MEP was associated with the use of cosmetics and personal care products. Higher ratios of BPS/BPA were observed in younger and more highly educated women. A shift in consumption from BPA to BPS was found in more urbanized region than others. Cumulative risk assessment for phthalates and bisphenols showed limited health risks.